The Classification of the Transfer of Intellectual Property Rights Under a Franchise Agreement for Purposes of Consumption Tax (VAT) : India and South Africa Compared - Van Zyl, Fanie; Visser, Coenraad (Comparative and International Law Journal of Southern Africa, 2020)
Modern consumption tax systems, generally, differentiate between the supply of goods and services. As the intrinsic nature of goods and services differ, different tax rules apply to tax the sale, transfer, supply, or consumption of goods and services. Changes in science and technology, and new and innovative business trends, often lead to transactions that escape the tax collector. For consumption tax purposes, a further distinction between the various types of goods and services is necessary in order to avoid the erosion of the tax base. Also, special tax rules apply to the different classifications of goods and services. This is particularly so in jurisdictions with variable tax rates. It is, therefore, key to classify the transaction or product appropriately to apply the appropriate tax rules and rates. This article compares the classification of the transfer of intellectual property rights for purposes of service tax and sales tax in India and the classification of the transfer of intellectual property rights for purposes of value-added tax (VAT) in South Africa. In addition we briefly canvass the general classification of intellectual property rights.